Cardiac Involvement in an Interesting Family of Myofibrillar Myopathy (Academia Journal of Medicine, 2022)
Myofibrillar myopathy primarily affects skeletal muscles; in some cases the heart muscle is also affected. The signs and  symptoms of MFM vary among affected individuals, typically dependent on the exact genetic cause of the disease. Most people with this  disease begin to develop muscle weakness (myopathy) in mid adulthood. However features of this disease can appear anytime between infancy  and late adulthood. We here present a family of patients with history of muscle weakness and cardiac involvement.
Keywords: Myofibrillar myopathy; Muscle weakness; Cardiomyopathy; Desmin